Chemical Pressure-Induced enhancement of electrochemical performance in Ni1-X CuxTe2 (X = 0 and 0.10) layered compounds - Rajkumar Sokkalingam; Manikandan Krishnan; Jesman Sthevan Kovil Pitchai; Sivakumar Periyasamy; Arjun Kumar Bojarajan; Arumugam Sonachalam; Sambasivam Sangaraju (Electrochemistry Communications)
This article employed the self-flux technique to successfully generate single crystalline Ni1-XCuXTe2 (X = 0 and 0.10) for electrochemical applications. The X-ray powder diffraction (XRPD) patterns revealed that both compounds have a CdI2-type trigonal structure with a P3m1 space group. The field emission scanning electron microscope (FESEM) images depicted the layered structure of these compounds. The elemental composition was analyzed via X-ray photoelectron spectroscopy (XPS). The electrochemical measuring results demonstrated that the Ni1-XCuXTe2 (X = 0 and 0.10) composite electrodes exhibit improved electrocatalytic activity, with 360 and 544 F/g capacitances, respectively. This enhancement in electrochemical performance is attributed to the addition of Cu doping and the presence of many flaws. Furthermore, Ni1-XCuXTe2 (X = 0 and 0.10) electrodes exhibited high electrochemical stability in supercapacitors (SCs). These findings suggest that the Ni1-XCuXTe2 (X = 0 and 0.10) compounds are promising candidates for SCs with increased capacitance and stability. The combination of structural properties, Cu doping, and defect-induced enhancement led to better electrochemical performance.